2013
DOI: 10.5194/isprsarchives-xl-1-w2-305-2013
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Multitemporal Thermal Orthophotos From Uav Data

Abstract: ABSTRACT:The paper deals with using a TIR camera on an UAV for acquiring multitemporal thermal images of a building block against the background of detecting, monitoring and analysing urban heat islands. It is motivated by a research project called EO2HEAVEN (Earth Observation and Environmental Modelling for the Mitigation of Health Risks) which analyses the influence of environmental effects to human health. Therefore, the aim is the generation of thermal orthophotos from UAV data which can be used for furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 6 publications
0
16
0
1
Order By: Relevance
“…Unfortunately, processing of thermal data with SfM does not always work flawlessly, and several studies have reported that SfM was not able to align thermal datasets properly [14,25,34]. In these cases, thermal maps could not be created or were created manually, by mosaicking separate images which were georeferenced manually using GCPs.…”
Section: )mentioning
confidence: 99%
“…Unfortunately, processing of thermal data with SfM does not always work flawlessly, and several studies have reported that SfM was not able to align thermal datasets properly [14,25,34]. In these cases, thermal maps could not be created or were created manually, by mosaicking separate images which were georeferenced manually using GCPs.…”
Section: )mentioning
confidence: 99%
“…As for the descriptor, Samantha implements a 128-dimensional radial descriptor (similar to the log-polar grid of GLOH described by (Mikolajczyk and Schmid, 2005)), based on the accumulated response of steerable derivative filters. This combination of detector/descriptor performs in a comparable way to SIFT (Lowe, 2004), which is proved to be well suited for features detection also in low resolution thermal imagery (Pech et al, 2013), and at the same time avoids patent issues. Only a given number of key-points with the overall strongest response are retained.…”
Section: Structure-and-motionmentioning
confidence: 99%
“…The geometric calibration of a thermographic camera has been studied in some works (Luhmann et al, 2013, Lagüela et al, 2011. (Hoegner and Stilla, 2015) propose a method for automatic texturing of building * Corresponding author facades from terrestrial thermal infrared image sequences, while (Pech et al, 2013) analyze the problem of using a TIR camera on an UAV for acquiring multi-temporal thermal images and generating thermal orthophotos. In (Khodaei et al, 2015) it is demonstrated that Digital Surface Models (DSM) generated from aerial thermal imagery can have comparable accuracy with respect to the one derived from visible images, while in (Hoegner et al, 2014) a fusion of time-of-flight depth images and TIR images is used to create an accurate 3D point cloud for subsequent scene segmentation and people detection.…”
Section: Introductionmentioning
confidence: 99%
“…For most modern RGB cameras, a typical UAV flight campaign acquires enough sharp and properly illuminated images and therefore the unknown camera calibration coefficients are estimated during the image alignment step, always under the assumption enough tie points are found. The workflow for the interior calibration of thermal cameras is well documented in the literature (Luhmann et al, 2010, Hartmann et al, 2012, Pech et al, 2013. Although most authors recommend to use an aluminum plate with coded targets or similar structures to get significant thermal reflection differences, it turned out that also printed paper is sufficient.…”
Section: Geometric Camera Calibrationmentioning
confidence: 99%